2019
DOI: 10.1002/cam4.2131
|View full text |Cite
|
Sign up to set email alerts
|

The development and external validation of simplified T category classification for nasopharyngeal carcinoma to improve the prognostic value in the intensity‐modulated radiotherapy era

Abstract: Background Intensity‐modulated radiotherapy (IMRT) provides excellent local control in nasopharyngeal carcinoma (NPC). We investigated whether simplifying 8th American Joint Committee on Cancer staging system T categories improves prognostic value. Methods We used 2191 NPC patients as a training set and 414 patients separately as an independent, external validation cohort. Results In the training set, local relapse‐free survival (LRFS), disea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…Indeed, Tang et al proposed a simplified T classification (ie, merging T2 and T3 into T2), and confirmed that significant differences in OS, LRFFS, and DFS could be found using the new T categories both in a training set and an external validation cohort. [ 25 ] Moreover, the new stages generated by regrouping the T and N classifications showed significant differences in OS and DFS. [ 25 ]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, Tang et al proposed a simplified T classification (ie, merging T2 and T3 into T2), and confirmed that significant differences in OS, LRFFS, and DFS could be found using the new T categories both in a training set and an external validation cohort. [ 25 ] Moreover, the new stages generated by regrouping the T and N classifications showed significant differences in OS and DFS. [ 25 ]…”
Section: Discussionmentioning
confidence: 99%
“…[ 25 ] Moreover, the new stages generated by regrouping the T and N classifications showed significant differences in OS and DFS. [ 25 ]…”
Section: Discussionmentioning
confidence: 99%
“…With the technological advances in both diagnostics and treatment, the differences in survival and local control in the T-category has diminished. Eight of the included studies proposed the simplification of the T-category (6,(21)(22)(23)(24)(25)(26)(27); these included three studies that suggested the merging of T1 and T2 disease (21,23,24), one suggested combining of T1, T2, and T3 disease (22), and one proposed a merging of T2 and T3 (27). Other studies proposed simplification of the definition of Tclassification, refinement of T2-T4 disease, and reclassification as T1 and T2 only (6,25,26).…”
Section: T-classificationmentioning
confidence: 99%
“…Particularly, the prognostic value of the T category is weaker than the previous. Even though modifications have been made in the updated staging system, it is still challenging to predict local control purely based on this system [ 9 ].…”
Section: Introductionmentioning
confidence: 99%